SERVICE QUALITY OF ANTENATAL CARE SERVICES WITH MIDWIFE BEHAVIOR - Wardani, Ratih Kusuma; Ratna Feti Wulandari; Vide Bahtera Dinastiti (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2021)
Midwifery services are an effort to reduce maternal mortality. In Indonesia, there are still high obstetric complications due to the low number of ANC visits caused by pregnant women who are not satisfied with the services provided by midwives who provide services. The purpose of this study was to determine the relationship between the service quality of the assurance dimension and the behavior of midwives in ANC services. The research design used was correlational analytic with a cross sectional approach. The subjects studied were pregnant women in February – July as many as 30 respondents. The instruments used are questionnaires and check lists, data analysis using the Spearman rho test. The results of the study obtained was a relationship between the quality of service in the assurance dimension and the behavior of midwives in ANC services. The conclusion is that the better the quality of service, the better the behavior of the midwife. With many clients who are still not satisfied with ANC services at Polindes, it is necessary to improve the quality of services that must be provided to consumers in midwifery services by way of midwives being more active in participating in training and training.